Теоретичне визначення політичних конфліктів у сучасній Україні - Білецька, Ю. В.; Билецкая, Ю. В.; Bileckaja, Ju. (My University, 2013)
A question of political conflict is the issue of the day, both in Ukraine and in the world. This type of conflicts acquires global scales, and that is why there is a requirement in the perfect study of such phenomenon. For creation of mechanism of the rapid reacting on such type of conflicts for our state it is needed to define the features of political conflicts in Ukraine.
Білецька Ю. В. Теоретичне визначення політичних конфліктів у сучасній Україні / Ю. В. Білецька // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 199-207.
Keywords: політичний конфлікт; механізм швидкого реагування на політичний конфлікт; особливості політичних конфліктів в Україні; политический конфликт; механизм быстрого реагирования на политический конфликт; особенности политических конфликтов в Украине; political conflict; rapid response mechanism in the political conflict; especially political conflicts in Ukraine